Three new species of genus Sinophorus Förster (Hymenoptera, Ichneumonidae) parasitizing twig and defoliating Lepidoptera - Sheng, Mao-Ling; Li, Tao; Cao, Jiang-Feng (Zootaxa, 2015)
Three new wasp species are described from the subfamily Campopleginae (Hymenoptera: Ichneumonidae), Sinophorus bazariae Sheng, sp. n., reared from Bazaria turensis Ragonot (Lepidoptera, Pyralidae) in Dulan County, Qinghai Province, China, S. nigrus Sheng, sp. n., reared from Epinotia rubiginosana rubiginosana (Herrich-Schäffer) (Lepidoptera, Tortricidae) in Weichang, Hebei Province, and S. zeirapherae Sheng, sp. n., reared from Zeiraphera grisecana (Hübner) (Lepidoptera, Tortricidae) in Liupanshan, Ningxia Hui Autonomous Region. A key to the species of Chinese Sinophorus is provided.